2023
DOI: 10.5603/cj.a2021.0012
|View full text |Cite
|
Sign up to set email alerts
|

In-hospital outcome of re-attempted percutaneous coronary interventions for chronic total occlusion

Abstract: Background: With the advent of novel recanalization techniques and emerging devices, percutaneous coronary intervention (PCI) has become a promising leading treatment option for patients with chronic total occlusions (CTO). The present study aims to evaluate the acute outcomes of PCI in previously failed re-attempted vs. first-attempted CTO-lesions. Methods: Between 2012 and 2019, 619 patients were included and treated with PCI of at least one CTO. 253 patients were re-attempted lesions, while 366 were initial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 33 publications
(40 reference statements)
0
2
0
Order By: Relevance
“…Sachdeva et al [21] further reported that all patients with occluded coronary arteries showed an ischemic fractional flow reserve, even with severe regional dysfunction or well-developed collaterals. 9 Nowadays, PCI is becoming the preferred revascularization method due to the rapid advancement in equipment and techniques as well as a growing expertise among dedicated operators [22][23][24][25][26][27]. The rate of successful CTO PCI has increased to 90% in experienced institutions [28].…”
Section: Discussionmentioning
confidence: 99%
“…Sachdeva et al [21] further reported that all patients with occluded coronary arteries showed an ischemic fractional flow reserve, even with severe regional dysfunction or well-developed collaterals. 9 Nowadays, PCI is becoming the preferred revascularization method due to the rapid advancement in equipment and techniques as well as a growing expertise among dedicated operators [22][23][24][25][26][27]. The rate of successful CTO PCI has increased to 90% in experienced institutions [28].…”
Section: Discussionmentioning
confidence: 99%
“…A composite endpoint was evaluated including acute cardiac death, vascular and bleeding complications, coronary perforation, which necessitated treatment by pericardial puncture, peri-interventional myocardial infarction (MI) which was defined as an increase in cardiac troponin blood levels in a patient who also exhibits signs or symptoms of MI, stroke and emergency coronary artery bypass grafting surgery (CABG) [ 19 , 20 ].…”
Section: Methodsmentioning
confidence: 99%